2006
DOI: 10.1093/jac/dkl173
|View full text |Cite
|
Sign up to set email alerts
|

Human intravenous immunoglobulin for experimental streptococcal toxic shock: bacterial clearance and modulation of inflammation

Abstract: IVIG monotherapy can confer benefit in experimental streptococcal shock, but extension of these findings to the clinical situation will require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 28 publications
6
52
0
Order By: Relevance
“…Many of these have sought to prevent or disrupt the formation of MHC-II/SAg/TCR complexes. These have ranged from explorations of active immunization with inactivated recombinant SEB vaccines (5, 26, 52), synthetic peptides (53), and proteasome-SEB toxoid combinations (29,30) to investigations of antibody-based passive immunoprophylaxis/immunotherapy (9,10,21,23,38,49), as well as synthetic peptides antagonists (1-3) and receptor mimics such as chimeric mimics of MHC-II-TCR (19,27,36) and of the TCR V␤ (7). Although all of these approaches have shown some promise, based on the long history of clinical experience with the use of antibodies, our approach has focused on demonstration of an approach to the derivation of forms of monoclonal anti-SEB antibodies that might be suitable for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these have sought to prevent or disrupt the formation of MHC-II/SAg/TCR complexes. These have ranged from explorations of active immunization with inactivated recombinant SEB vaccines (5, 26, 52), synthetic peptides (53), and proteasome-SEB toxoid combinations (29,30) to investigations of antibody-based passive immunoprophylaxis/immunotherapy (9,10,21,23,38,49), as well as synthetic peptides antagonists (1-3) and receptor mimics such as chimeric mimics of MHC-II-TCR (19,27,36) and of the TCR V␤ (7). Although all of these approaches have shown some promise, based on the long history of clinical experience with the use of antibodies, our approach has focused on demonstration of an approach to the derivation of forms of monoclonal anti-SEB antibodies that might be suitable for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…More recently the successful use of polyclonal human intravenous immunoglobulin (IVIG) for the treatment of invasive infections has been demonstrated in numerous in vitro studies [12,[115][116][117][118]. However, the use of IVIG as an adjunctive treatment in a clinical setting has been less promising [119,120].…”
Section: Novel Therapeutics For the Treatment Of Invasive S Pyogenesmentioning
confidence: 99%
“…The advent of the HLA class II transgenic (HLA-tg) mice provided an opportunity to study the pathogenesis of GAS in a readily manipulated animal model with a sensitivity to SAgs similar to that of humans (22)(23)(24)(25)(26). Indeed, several studies have shown that HLA-tg mice mount potent responses to GAS SAgs (20,23,25,27,28).…”
mentioning
confidence: 99%